If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(c + 5) + 3(2c + 2) = 2 + 2(3c + 10) Reorder the terms: 2(5 + c) + 3(2c + 2) = 2 + 2(3c + 10) (5 * 2 + c * 2) + 3(2c + 2) = 2 + 2(3c + 10) (10 + 2c) + 3(2c + 2) = 2 + 2(3c + 10) Reorder the terms: 10 + 2c + 3(2 + 2c) = 2 + 2(3c + 10) 10 + 2c + (2 * 3 + 2c * 3) = 2 + 2(3c + 10) 10 + 2c + (6 + 6c) = 2 + 2(3c + 10) Reorder the terms: 10 + 6 + 2c + 6c = 2 + 2(3c + 10) Combine like terms: 10 + 6 = 16 16 + 2c + 6c = 2 + 2(3c + 10) Combine like terms: 2c + 6c = 8c 16 + 8c = 2 + 2(3c + 10) Reorder the terms: 16 + 8c = 2 + 2(10 + 3c) 16 + 8c = 2 + (10 * 2 + 3c * 2) 16 + 8c = 2 + (20 + 6c) Combine like terms: 2 + 20 = 22 16 + 8c = 22 + 6c Solving 16 + 8c = 22 + 6c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6c' to each side of the equation. 16 + 8c + -6c = 22 + 6c + -6c Combine like terms: 8c + -6c = 2c 16 + 2c = 22 + 6c + -6c Combine like terms: 6c + -6c = 0 16 + 2c = 22 + 0 16 + 2c = 22 Add '-16' to each side of the equation. 16 + -16 + 2c = 22 + -16 Combine like terms: 16 + -16 = 0 0 + 2c = 22 + -16 2c = 22 + -16 Combine like terms: 22 + -16 = 6 2c = 6 Divide each side by '2'. c = 3 Simplifying c = 3
| 7(1-3m)=39+2m | | 6.5=2.5t-11 | | 80000-.25x=x | | -x-6(x+8)=-36-4x | | t(4-1)+9=27 | | 5(2+3w)-1=-6 | | 5(2z-1)-4(z+3)=4(z+1) | | 6(6+6v)=36-v | | (2+3w)-1=-6 | | 6y=5 | | (x+2)(x-2)=1 | | -28=196x | | 80000-2x=x | | -6x+4x=-12 | | 8.69=-1-4.7x-x | | 5(2z-1)-4(2+3)=4(2+1) | | 4x=-1+2(x+1) | | 14-(x+5)=4x-6 | | 8-5x=x-16 | | 2(x+3)-5[4-(x-6)]=x+2 | | 4+9=-8+-13 | | 2x+8y=24 | | 4y-6=-2y-11 | | xsuared=x-6 | | -2(5n+2)=4 | | -2.25=-2.6x+0.16 | | g/10+14=5 | | 3(5a-4)= | | 4(3.14)=w-6(3.14) | | 8+3t=4 | | 4x+2y=250 | | 9.5=3.6n+1+2n |